2015
DOI: 10.15196/rs05107
|View full text |Cite
|
Sign up to set email alerts
|

New trajectories of the Hun garian regional development: balanced and rush growth of territorial capital

Abstract: The basic assumption of the paper is that numerous similarities exist between the patterns of economic growth and territorial capital growth. The rush economic growth and rush growth of territorial capital are compared empirically at Hungarian micro-regional level from 2004 until 2010. After normalizing the dataset, a very novel spatial econometric method is applied, called a penalty for bottleneck. The results show that the constant rush growth of territorial capital is as harmful as economic recession. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…In another Hungarian paper, Jóna (2015b) took into consideration the peculiarities of the rapid growth of territorial capital and its influence on the state of the economy of Hungarian micro-regions during the period from 2004 until 2010. By applying spatial econometrics, the author found that the rapid increase of territorial capital causes negative changes at the country's regional level.…”
Section: Empirical Evidence On the Territorial Capital Approach: A Short Overviewmentioning
confidence: 99%
“…In another Hungarian paper, Jóna (2015b) took into consideration the peculiarities of the rapid growth of territorial capital and its influence on the state of the economy of Hungarian micro-regions during the period from 2004 until 2010. By applying spatial econometrics, the author found that the rapid increase of territorial capital causes negative changes at the country's regional level.…”
Section: Empirical Evidence On the Territorial Capital Approach: A Short Overviewmentioning
confidence: 99%
“…A területitőke-koncepción alapuló vizsgálatok szerint a magyarországi lokális gazdasági fejlődés kulcsfontosságú tényezői közül ki kell emelni a kis-és középvállalkozá-sok (kkv-k) 1 együttműködését, illetve hálózatosodását, továbbá azt, hogy a regionális növekedés forrásainak rangsorában az endogén kapacitások előrébb állnak, mint az exogén források (Jóna 2015a, 2015b, Stimson-Stough-Nijkamp 2011, Stimson 2014. A globális-lokális paradoxon szerint egyre fontosabb az endogén tényezők felismerése…”
Section: Bevezetőunclassified